Production Characteristics of All‐male and Mixed‐sex Giant River Prawns, Macrobrachium rosenbergii, Grown in Earthen Ponds in Kentucky and Mississippi USA. Issue 2 (April 2015) - Tidwell, James H.; D'Abramo, Louis R.; Coyle, Shawn D.; Bright, Leigh A.; Shultz, Charlie; Kupchinsky, Zachary; Schwartz, Pamela; Upstrom, Craig
Abstract Production and population characteristics of monosex male (all‐male) giant river prawns, Macrobrachium rosenbergii, were compared with a normal (mixed‐sex) population in separate studies in Mississippi and Kentucky (USA) under low and high density stocking conditions, respectively. In Study 1 (Mississippi), juvenile prawns were stocked into eight 0.05–0.06 ha ponds at 24, 700/ha. The mean stocking weight of all‐male was 0.34 g and mixed‐sex was 0.39 g. Prawns were fed 23% crude protein "range cubes" and harvested after 120 d for the all‐male prawns and 112 d for mixed‐sex prawns. In Study 2 (Kentucky), juvenile prawns from each group were stocked into six 0.04 ha ponds at 60, 000 juveniles per hectare. The mean stocking weight for all‐male was 0.38 g and for mixed‐sex juveniles was 0.34 g. Prawns were fed a commercial sinking pellet (33% protein) once daily at a standardized rate and harvested after 105 d. In both locations survival of mixed‐sex prawns and all‐male prawns was not significantly different and the final average weight of all‐male prawns was significantly greater than the average weight of mixed‐sex prawns. For the study in Kentucky, total production was not significantly different between treatments, whereas in Mississippi total production in the all‐male ponds was significantly higher than in the mixed‐sex ponds. For both studies, the production size index of all‐male prawns was significantly greater than that of mixed‐sex prawns. In terms of population structure, in all‐male ponds there was a significant increase in orange claw (OC) males compared with the mixed‐sex ponds both as a percent of sex and a percent of total population. The increase in OC numbers in all‐male populations may be due to a lack of females to stimulate the transition of males to the final, sexually mature, blue claw stage. As target weights increase from 20, 30, and 40 g, the all‐male populations were increasingly superior in terms of production (kg/ha) of those target sizes. The economic benefit of all‐male over mixed‐sex populations will be principally based on an examination of tradeoffs that primarily consider the cost difference of juveniles relative to the price differences for different final harvest weights.